The Impact of Sharia Economics on The Vision of A Golden Indonesia 2045 - Hidayat, Aly; Akbar, Wahyu; Ardiansyah, Mawar; Adriana Binti Ibrahim, Elly (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2024)
This study aims to explore the potential of Sharia economics in supporting sustainable economic growth and resilience in Indonesia, particularly in the context of the Golden Indonesia 2045 vision. Despite existing research focusing on specific aspects of Sharia economics, such as its impact on MSMEs, poverty reduction, or Fintech, there remains a gap in comprehensively assessing its long-term contribution to national development. This research addresses this gap by offering a holistic analysis of how Sharia economic principles can foster financial inclusion, poverty alleviation, and economic resilience while providing policy recommendations for expanding its role in Indonesia's broader development strategy. The study employs a literature review as the primary research method, analyzing relevant academic journals, books, policy reports, and official documents. The findings suggest that Sharia economics, through instruments such as microfinance, MSME financing, zakat, and productive waqf, can drive inclusive and sustainable economic growth. Also, halal industries and Islamic tourism offer significant opportunities to expand Indonesia's economic base and enhance its global competitiveness. However, limitations such as the lack of primary data (e.g., surveys or interviews) to evaluate the direct impact of Sharia economics on community welfare highlight areas for future research. Further studies integrating primary data and comparative analysis with other countries can provide deeper insights into optimizing Sharia economics for Indonesia’s future development.